BUSINESS PLAN SEBAGAI IMPLEMENTASI KEWIRAUSAHAAN PADA PEMBELAJARAN EKONOMI DI SMA (Dinamika Pendidikan, 2013)
The purpose of this study was to investigate the implementation of businessplan on the materials of Entrepreneurship in Economics Studies at SMA Negeri 1Wonosobo. The respondents were all students of class X at SMA Negeri 1 Wonosobo.The data were collected by observation, interviews and questionnaires. Then, the datawere analyzed descriptively. The result of the research showed that 10th grade studentsat SMA Negeri 1 Wonosobo have implemented entrepreneurial spirit by composing thebusiness plan.